Analysis of Company Performance with The Balanced Scorecard Perspective Approach to Improving The HR Of PT. Pos Indonesia (Persero) Cimahi - Permatasari, Bela Hanisyah; Nurafrianti, Lesta; Ramadhan, Taufik; Miskun, Aden Naufal; Istambul, Muhammad Rozahi (International Journal of Psychosocial Rehabilitation, 2020)
Balanced scorecard is an alternative performance measurement that aims to combine financial and non- financial performance measures. This measurement is the result of a process based on the mission and strategy of a company. In facing the transformation of the information age competition, changes in the business environment have prompted companies to re-evaluate how to manage the business so that they can compete and generate revenue as targeted by the company. Companies need to monitor various aspects of performance measurement to achieve profit competitiveness in the future. Many companies still make the financial side which is used as a benchmark of the company's strategic plan. Financial valuations are no longer enough to reflect actual performance. With this we need a performance measurement method that can assess company performance accurately and comprehensively with the Balanced Scorecard concept that measures company performance from four perspectives, namely financial perspective, customer perspective, internal business perspective and finally the growth and learning perspective. The results of this study are the company's performance on a financial perspective produces poor performance results, the performance of PT. Pos Indonesia Cimahi from a customer perspective shows better results. From the perspective of internal business processes, the improvement of the company's performance is getting better. Based on the measurements made, that the company's performance in the perspective of learning and growth shows better results.